2009
DOI: 10.1007/s10661-009-1225-x
|View full text |Cite
|
Sign up to set email alerts
|

Post tsunami changes in soil properties of Andaman Islands, India

Abstract: A post tsunami study was conducted to assess the changes in soil properties in the Andaman Island, in India. The present study reported tsunami led conversion of acid soils to saline acid soils and acid sodic soils to acid saline sodic soils in the areas South Andaman inundated during tsunami and permanently receded later and in the low-lying area submerged during high tides. Upon intense leaching acid saline soils and acid saline sodic may further develop typical characteristics of acidic soils and acidic sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Our observation is in agreement with the studies summarized in Table 1 that microbial communities were different between tsunami deposited sediments and non-tsunami soils and sediments. Similar to Nayak et al 25 , Asano et al 28 , Godson et al 26 , and Somboonna et al 29 , we observed that tsunami deposits have relatively lower diversity as compared to nontsunami soils and sediments (Fig. 3).…”
Section: Do Microbial Communities Differ Between the Respective Study Sites And Samples?supporting
confidence: 89%
See 2 more Smart Citations
“…Our observation is in agreement with the studies summarized in Table 1 that microbial communities were different between tsunami deposited sediments and non-tsunami soils and sediments. Similar to Nayak et al 25 , Asano et al 28 , Godson et al 26 , and Somboonna et al 29 , we observed that tsunami deposits have relatively lower diversity as compared to nontsunami soils and sediments (Fig. 3).…”
Section: Do Microbial Communities Differ Between the Respective Study Sites And Samples?supporting
confidence: 89%
“…There is a considerable amount of literature describing how microbial communities in different environmental settings respond to abrupt and intense "pulse" disturbances (i.e. relatively short-duration and discrete environmental alterations) 23 due to catastrophic events such as coastal flooding 21,[24][25][26][27][28][29] , wildfire 30,31 , earthquake 32,33 . The primary aim of such studies is commonly to investigate how microbes respond to a disturbance in nutrients 21,[28][29][30] , water resources 24,25 , substrate availability 25,[27][28][29][30][31][32] , or other physical environment changes 23,[31][32][33] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nayak et al (2010) measured exchangeable Al and analysed iron fractionation. They concluded that the tsunami caused the conversion of acid soils to saline acid soils and sodic soils to acid saline sodic soils, and that the tsunami not only caused soil salinity but also affected Fe mobility Ilayaraja et al (2012).…”
mentioning
confidence: 99%